2019
DOI: 10.1091/mbc.e18-09-0584
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle–dependent association of polo kinase Cdc5 with CENP-A contributes to faithful chromosome segregation in budding yeast

Abstract: Evolutionarily conserved polo-like kinase, Cdc5 (Plk1 in humans), associates with kinetochores during mitosis; however, the role of cell cycle–dependent centromeric ( CEN) association of Cdc5 and its substrates that exclusively localize to the kinetochore have not been characterized. Here we report that evolutionarily conserved CEN histone H3 variant, Cse4 (CENP-A in humans), is a substrate of Cdc5, and that the cell cycle–regulated association of Cse4 with Cdc5 is required for cell growth. Cdc5 contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…We next examined if the N-terminus of Cse4 is required for the SDL of GAL-CSE4 in met30-6 and cdc4-1 strains. The rationale for this is based on the essential role of the N-terminus for its interactions with kinetochore proteins, Ub-mediated proteolysis and post-translational modifications (PTMs) of Cse4 [19,26,27,[54][55][56][57][58][59][60][61][62]. Furthermore, we recently showed that hir mutants, which are defective in proteolysis of overexpressed Cse4, are sensitive to GAL-CSE4 but not GAL-cse4Δ129 (Cse4 lacking the N-terminal domain) [33].…”
Section: Mutants Of Scf-met30 and Scf-cdc4 Exhibit Sdl With Overexprementioning
confidence: 99%
“…We next examined if the N-terminus of Cse4 is required for the SDL of GAL-CSE4 in met30-6 and cdc4-1 strains. The rationale for this is based on the essential role of the N-terminus for its interactions with kinetochore proteins, Ub-mediated proteolysis and post-translational modifications (PTMs) of Cse4 [19,26,27,[54][55][56][57][58][59][60][61][62]. Furthermore, we recently showed that hir mutants, which are defective in proteolysis of overexpressed Cse4, are sensitive to GAL-CSE4 but not GAL-cse4Δ129 (Cse4 lacking the N-terminal domain) [33].…”
Section: Mutants Of Scf-met30 and Scf-cdc4 Exhibit Sdl With Overexprementioning
confidence: 99%
“…We chose to further investigate Cdc5 for multiple reasons. First, we previously identified Cse4 as a substrate of Cdc5 [27]. Second, Cdc5 has been shown to interact with both Cse4 and Ndc80 [25] and phosphorylate microtubule-associated proteins (MAPs) such as Stu2 and Slk19 [40] and the SAC component Mad3 [41].…”
Section: Constitutive Cdc5 Kinase Activity At Different Kinetochore Smentioning
confidence: 99%
“…Polo kinase is characterized by a N-terminal catalytic kinase domain that is flexibly linked to a binding domain called Polo-box domain (PBD) whose key function is to target the kinase domain to its substrates by binding preferentially phosphosites that have previously been phosphorylated by another kinase, most commonly by cyclin-dependent kinase (CDK) or Polo kinase itself (reviewed in [24]). Budding yeast Polo kinase, Cdc5, is known to interact with kinetochore proteins [25] and localize at centromeres in mitosis [26,27]. In our prior work we found that forced Cdc5 recruitment to the MIND complex resulted in a growth defect and chromosomal instability [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study from the Basrai lab indicates that the centromeric histone H3 variant Cse4 interacts with Cdc5 to enable centromere recruitment of Cdc5. In turn, Cdc5 phosphorylates Cse4, and this phosphorylation further stimulates centromere recruitment of inner kinetochore protein Mif2 as well as cohesin [49]. Therefore, Cdc5-mediated Cse4 phosphorylation helps kinetochore assembly and cohesion establishment at centromeres.…”
Section: Cdc5 Kinasementioning
confidence: 99%